Dickkopf‐4 gene expression is associated with differentiation and lymph node metastasis in colorectal cancer. Issue 5 (10th April 2019) - Tsukui, Yuya; Yamaguchi, Tatsuya; Maekawa, Shinya; Takano, Shinichi; Sato, Tadashi; Enomoto, Nobuyuki
Abstract : Background and Aim: Although high expression of Dickkopf‐4 (DKK‐4) in colorectal cancer has been reported in previous studies, its impact on clinicopathological features, including the prognosis and mechanism of expression, has not been well clarified to date. Methods: (i) DKK‐4 protein expression was analyzed by immunohistochemical staining with anti‐DKK‐4 antibody using archived formalin‐fixed paraffin‐embedded specimens obtained at surgery from 122 patients with colorectal cancer, and its association with clinicopathological findings was also investigated. (ii) The association between intratumoral DKK‐4 protein expression and somatic hotspot mutations in cancer‐associated genes in 40 patients was investigated using a next‐generation sequencer. Results: In cross‐section, DKK‐4 protein expression in colorectal tissue was related to an adenocarcinoma of a histologically differentiated type (tub1/tub2, P = 0.032) and distant metastasis ( P = 0.012). Longitudinally, however, DKK‐4 was not an independent prognostic factor determining overall survival (OS). On the other hand, in patients with metastasis, high DKK‐4 protein was independently associated with short OS ( P = 0.013). In addition, colorectal cancer tissue with high DKK‐4 protein expression was associated with hotspot mutations in Wnt/β catenin‐signaling molecules (APC, CTNNB1, and FBXW7, P = 0.03). Conclusion: Intratumoral DKK‐4 expression, by partly reflecting the Wnt/β catenin pathway, is strongly associated with the advancement of colorectal cancer and OS in colorectal cancer patients with metastasis, although further studies are needed. Abstract : In this study, by analyzing 122 archived colorectal cancer tissues, we demonstrated that intratumoral DKK‐4 expression was related to an adenocarcinoma of a histologically differentiated type (tub1/tub2, P = 0.032) and distant metastasis ( P = 0.012) by partly reflecting the Wnt/β catenin pathway. Moreover, we also demonstrated that intratumoral DKK‐4 protein was significantly associated with short overall survival in patients with metastasis ( P = 0.013) or with lymph node metastasis ( P = 0.010). These results suggest that DKK‐4 could be a useful biomarker in clinical practice in colorectal cancer patients.